2011
DOI: 10.3758/s13414-011-0249-9
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual interactions depend on context of congruency

Abstract: In this study, we addressed how the particular context of stimulus congruency influences audiovisual interactions. We combined an audiovisual congruency task with a proportion-of-congruency manipulation. In Experiment 1, we demonstrated that the perceived duration of a visual stimulus is modulated by the actual duration of a synchronously presented auditory stimulus. In the following experiments, we demonstrated that this crossmodal congruency effect is modulated by the proportion of congruent trials between (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 25 publications
(43 reference statements)
4
23
0
Order By: Relevance
“…The proposal that context-specific improvements in interference resolution reflect implicit “priming of control” is supported by findings suggesting that the behavioral phenomenon occurs in the absence of awareness regarding contextual variation of conflict frequency (Crump et al, 2006; Heinemann et al, 2009; Sarmiento et al, 2011). In line with these previous results, only one out of twenty-five participants in the current experiment reported noticing the location-based manipulation of conflict frequency in our post-test survey (Materials and Methods).…”
Section: Resultsmentioning
confidence: 97%
“…The proposal that context-specific improvements in interference resolution reflect implicit “priming of control” is supported by findings suggesting that the behavioral phenomenon occurs in the absence of awareness regarding contextual variation of conflict frequency (Crump et al, 2006; Heinemann et al, 2009; Sarmiento et al, 2011). In line with these previous results, only one out of twenty-five participants in the current experiment reported noticing the location-based manipulation of conflict frequency in our post-test survey (Materials and Methods).…”
Section: Resultsmentioning
confidence: 97%
“…This bewildering quality of dissonant music might further contribute to the information complexity of dissonant intervals, producing cognitive demands on the listener that consonant, harmonic music does not. Consistent with these possibilities is a large body of literature showing that behavioral responses to complex (Patten, Kircher, Oslund, & Nilsson, 2004), ambiguous (MacDonald, Just, & Carpenter, 1992), conflicting (Eriksen & Eriksen, 1974;MacLeod, 1991;Sarmiento, Shore, Milliken & Sanabria, 2012;Stroop 1935), and unexpected (Crump, Gong, & Milliken, 2006, Jonides 1981Posner, Snyder, & Davidson, 1980;) stimuli take more time and are often less accurate than responses to simple, unambiguous, non-conflicting, and expected stimuli.…”
Section: Introductionmentioning
confidence: 94%
“…Studies have suggested that changing the proportion of congruent trials will result in shifts in attentional control and will thus indirectly modulate the outcome of multisensory integration (Sarmiento et al, 2012). This indirect modulation effect has also been demonstrated when the spread of attention across modalities, space and time was investigated (Busse et al, 2005; Donohue et al, 2011; Fiebelkorn et al, 2010), as discussed in section 5 .…”
Section: Effects Of Endogenous Attentional Selectivity On Multisenmentioning
confidence: 99%